The Importance of the Image: Images in Philosophy - C. Meijns (Opticon1826, 2011)
Images do not find a tender home in philosophy. The main job of a philosopher is that of giving and assessing arguments in order to understand the world better, and most of this work is done by thinking, speaking, or writing things out as text. An image makes a bad argument, because, strictly speaking, it is neither premise nor conclusion. One occasionally finds that images permeate into philosophical discussions, often precisely to get a clearer view on how problematic aspects of reality might be understood. Three main roles for images can be distinguished in the literature: as models, test cases, or objects of inquiry.
Keywords: images